Profil Aktivitas Enzim Diastase pada Madu Produksi UMKM Lokal Berdasarkan Hasil Uji BPOM di Jambi - Desmita Adriani Syamsu; Ratnawita; Ayu Pratiwi Ayu; Agung Darmawati (Badan Pengawas Obat dan Makanan, 2022)
Honey is a healthy product often sought after during the Covid-19 pandemic. This is one factor that increases the number of honeys produced by SMEs. During 2019-2021, there was an increase in the number of requests for honey sample testing by business actors at the food chemical testing laboratory at the Indonesia FDA Provincial Office in Jambi. This study aims to determine honey's quality profile by testing the diastase enzyme's activity using a UV-Vis Spectrophotometer. This research is a retrospective experimental analysis to provide an overview of test results related to honey quality by observing the diastase enzyme's activity in honey. The test data were processed using SPSS 16 to determine the percentage of samples that met the requirements (MS) and did not meet the requirements (TMS). Then the data were analyzed by quantitative descriptive using a histogram comparison between honey samples with MS and TMS in 2019-2021. According to the Indonesian National Standard (SNI)-8664:2018, good honey has a diastase enzyme activity of at least 3 Diastase numbers (DN). A total of 84 samples tested showed that 78.6% is MS with diastase enzyme activity between 3 DN to 28 DN, and 21.4% is TMS. However, based on the data, it is known that the number of TMS samples has decreased. Strengthening cooperation between Indonesia FDA Provincial Office POM in Jambi and stakeholders is important to assist local honey businesses in improving the quality of their products. It includes assisting the honey harvesting process and controlling the temperature and pH of the environment to maintain the content of enzymes, vitamins, and minerals.